Financial Feasibility of Sweet Orange (Citrus sinensis) Farming in Dau District, Indonesia - Ady Hadi Utomo; Agnes Quartina Pudjiastuti; Jatmiko Setiaji (International Journal of Business and Quality Research, 2026)
Sweet oranges are a horticultural commodity that offers health benefits and is affordable for consumers. However, the agribusiness faces many challenges in various countries, including Indonesia. This study aims to analyze financial feasibility of sweet orange farming and its sensitivity to changes in price and production. Data were collected from 77 farmers selected using a simple random sampling method. Feasibility analysis was based on Benefit Cost Ratio (B/C), Break Even Point (BEP) of production and price, Payback Period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR). Sensitivity analysis was based on price and production fluctuations. The results showed that existing sweet orange farming is feasible because B/C > 0, BEP production < actual production, BEP price < actual price. Payback period of 6.12 years, NPV of 135.9493 million IDR and IRR of 48.3% strengthen feasibility of this farming. Even though orange prices and production have decreased by 10-15%, sweet orange farming remains feasible. If orange prices and production drop by 20%, the farming business is not feasible because IRR is ≤ 6%. Sustainability of sweet orange farming can be achieved if farmers can increase their yields and income by 1) implementing intercropping and rejuvenation, 2) obtaining facilitation from extension workers and the government to establish an integrated sweet orange tourism area, and assistance in rejuvenation.